Pengaruh ESG (Enviromental, Social, and Governance) Score dan Ukuran Perusahaan terhadap Return Saham Perusahaan yang Terdaftar di Indeks LQ45 Tahun 2021-2024 - Siti Koiriyah; Ahmad Idris; Agung Pambudi Mahaputra (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of ESG (Environmental, Social, and Governance) Score and Company Size on Stock Returns of Companies listed on the LQ45 Index in 2021-2024. This study uses a quantitative method using secondary data in the form of annual reports and sustainability reports of related companies. The sampling technique was carried out using the purposive sampling method. The sample in this study was obtained using a purposive sampling technique and obtained 8 companies in the 2021-2024 period. The results of the study indicate that ESG Score has a negative and insignificant effect on stock returns and Company Size (SIZE) has a positive and insignificant effect on stock returns. Simultaneously, both variables have a positive and insignificant effect on stock returns.